2009
DOI: 10.1080/15228860802578873
|View full text |Cite
|
Sign up to set email alerts
|

Non-Farm Activity and Production Efficiency of Farm Households in Egbeda Local Government Area, Oyo State

Abstract: This study analyzes the production efficiency of farm households exhibiting significant non-farm earnings in Egbeda Local Government Area of Oyo State. The data for the study were collected from 120 farm households selected through multistage random sampling. Data envelope analysis (DEA), which reveals production inefficiencies, was used to estimate the production efficiency of the farm households (DMUs) via the input-output bundle of each farm household (technical efficiency and scale efficiency) and the outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
0
0
1
Order By: Relevance
“…The observed variations was due to some regions having well developed fishery sectors and better management abilities of gender-related difficulties in agriculture and animal husbandry. Though women used ancestral land, the study also revealed interest of urban employed and wage earning women in fish farming in agreement with Idumah [42] and Oni et al [43] who reported that ownership of the farmed plot, education and social status had positive influences on farm productivity. Therefore, proximity of farms to ready markets would positively encourage investments in fish farming.…”
Section: Discussionsupporting
confidence: 86%
“…The observed variations was due to some regions having well developed fishery sectors and better management abilities of gender-related difficulties in agriculture and animal husbandry. Though women used ancestral land, the study also revealed interest of urban employed and wage earning women in fish farming in agreement with Idumah [42] and Oni et al [43] who reported that ownership of the farmed plot, education and social status had positive influences on farm productivity. Therefore, proximity of farms to ready markets would positively encourage investments in fish farming.…”
Section: Discussionsupporting
confidence: 86%
“…L'origine autochtone et le statut salarié représenteraient des atouts pour l'amélioration de la productivité. Selon Idumah (2006) et Oni et al (2009 la possession de la parcelle exploitée, l'éducation et le statut social influencent positivement la productivité des exploitations agricoles. Les productions enregistrées étant toujours meilleures chez les agriculteurs autochtones, propriétaires terriens et scolarisés.…”
Section: Production Des Fermes Piscicoles Appartenant Aux Femmesunclassified